2012
DOI: 10.1177/0021998311419876
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties and corrosion behaviour of fly ash particles reinforced AA 2024 composites

Abstract: Composites are most promising materials of recent interest. Metal matrix composites (MMCs) possess significantly improved properties compared to unreinforced alloys. There has been an increasing interest in composites containing low density and low cost reinforcements. Hence, composites with fly ash as reinforcement are likely to over come thecost barrier for wide spread applications in automotive and small engine applications. In the present investigation, AA 2024 alloy – 2 to 10 wt% fly ash composites were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(12 citation statements)
references
References 20 publications
1
10
1
Order By: Relevance
“…Kumar et al [40] reported that the porosity of less than 4% is in the acceptable level. Similarly, researchers reported that while increasing the reinforcements like BLA, RHA and fly ash in the composite the density of composites decreases and the porosity increases [17,[40][41][42].…”
Section: Effect Of Gsa and B 4 C On Density And Porositymentioning
confidence: 99%
“…Kumar et al [40] reported that the porosity of less than 4% is in the acceptable level. Similarly, researchers reported that while increasing the reinforcements like BLA, RHA and fly ash in the composite the density of composites decreases and the porosity increases [17,[40][41][42].…”
Section: Effect Of Gsa and B 4 C On Density And Porositymentioning
confidence: 99%
“…Baradeswarn et al [28] carried out extensive work on the effect of reinforcements particle size on the composites and found that the compressive strength increases with an increase in wt.% of fly ash attributed to the coring and microsegregation of the particles in the matrix phase, leading to strengthening brought about by the epitaxial grain growth and interstitial bonding between the atoms. Rao et al [29] found that the composites reinforced with graphite and alumina exhibit greater compression strength, ascribed to the effect of graphite which is a ceramic reinforcement, influencing the compression characteristics of the composites due to the effect of coring on the matrix composites. Rohatgi et al [30] characterised the effect of cenospheres on AZ91D aluminium alloy and reported that the tensile properties increase with the inclusion of reinforcements in the matrix, thereby improving its metal workability characteristics for aerospace applications, thus providing an inference that the fly ash is having a limiting effect on the strength beyond 5 wt.%.…”
Section: Introductionmentioning
confidence: 99%
“…Irregular accumulation and inappropriate disposal of fly ash will lead to the global impact of pollution. Utilization of FA as a reinforcement serves as a double advantage of a suitable alternative to reduce environmental pollution and reduction of the production cost of AMCs [4][5][6][7]. Among the many techniques available to produce AMCs, stir casting is a very widely used method.…”
Section: Introductionmentioning
confidence: 99%